2004
DOI: 10.1097/01.wcb.0000107730.66603.51
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Induces Abnormal Microvasculature in the Endoglin Heterozygous Mouse Brain

Abstract: Summary:Hereditary hemorrhagic telangiectasia (HHT), associated with brain arteriovenous malformations, is caused by a loss of function mutation in either the endoglin (HHT1) or activin receptor-like kinase 1 gene (ALK-1, HHT2). Endoglin heterozygous (Eng +/− )mice have been proposed as a disease model. To better understand the role of endoglin in vascular malformation development, we examined the effect of vascular endothelial growth factor (VEGF) hyperstimulation on microvessels in adult endoglin heterozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 22 publications
3
64
0
Order By: Relevance
“…Fluorescein-lycopersicin esculentum lectin (Vector Laboratories, Burlingame, CA) staining was used to identify capillaries. We chose lectin staining because our previous studies demonstrated that this method is reproducible and reliable (29,39,48,50). Sections were fixed with 4% paraformaldehyde (PFA) for 30 min, blocked with 5% normal blocking serum for another 30 min, and incubated overnight with 2 g/ml lectin at 4°C.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Fluorescein-lycopersicin esculentum lectin (Vector Laboratories, Burlingame, CA) staining was used to identify capillaries. We chose lectin staining because our previous studies demonstrated that this method is reproducible and reliable (29,39,48,50). Sections were fixed with 4% paraformaldehyde (PFA) for 30 min, blocked with 5% normal blocking serum for another 30 min, and incubated overnight with 2 g/ml lectin at 4°C.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Functional vessels were detected by staining for tomato lectin injected intracardially immediately before euthanasia, which allows for identification of vessels receiving active blood flow 18,21 and precludes nonspecific labeling of microglia. In the CTX of control animals, the number of functional vessels continuously rose through postnatal day 21 ( Figure 1C-D), reflecting ongoing neovascular formation during postnatal development.…”
Section: Functional Neovascularization Is Decreased After Hypoxia/iscmentioning
confidence: 99%
“…Functional vessels were identified by transcardial administration (5 minutes before euthanasia) of biotinylated-lycopersicin esculentum lectin (tomato lectin, 1.25 mg/kg; Vector Laboratories), which labels endothelial cells only in perfused vessels. 18 Lectin and BrdU stainings were visualized with fluorescence-streptavidin (1:2000; Vector Laboratories) and Cy3-conjugated secondary antibody using a Nikon microscope or Zeiss laser-scanning confocal microscope, respectively. Vessels that showed double labels of lectin and BrdU were counted in a square area (460ϫ460 mm) from the perilesion area (including the ischemic boundary), the distant area (Ͼ500 mm apart from the ischemic boundary), and contralateral area.…”
Section: Evaluation Of Functional Revascularizationmentioning
confidence: 99%
“…The model consists of focal hyperstimulation by VEGF 165 in the brain using adenovirusmediated DNA transduction, resulting in enhanced formation of cerebral microvessels. 19,20 Our model is not a model of BAVM, but it is characterized by some of the phenotypic features of BAVM lesional tissue. Therefore, use of this model is a first step to mechanistically examine key angiogenic pathways and their response to pharmacological manipulation.…”
mentioning
confidence: 99%